Analisis Hukum Mengenai Delik Penganiayaan yang Terbukti Secara Sah dan Menyakinkan dalam Pemeriksaan Persidangan di Pengadilan Negeri Jakarta Selatan: Studi Kasus Putusan No. : 689/Pid.B/2018/Pn Jkt.Sel - Robbika Murti, Tanfidzan; Manulu, Karto; Anton Rikmadani, Yudi (Jurnal Hukum dan Demokrasi (JHD), 2024)
In general, criminal acts against bodies in the Criminal Code are called "torture". Persecution regulated by the Criminal Code consists of: a. Persecution based on Article 351 of the Criminal Code which is broken down into: Ordinary maltreatment, Persecution resulting in serious injuries, Persecution resulting in the death of the person; b. Light maltreatment regulated by Article 352 of the Criminal Code; c. Premeditated maltreatment regulated by Article 353 of the Criminal Code with the following details: Causing serious injuries, resulting in the death of the person; d. Serious maltreatment regulated by Article 354 of the Criminal Code with the following details: resulting in serious injuries, resulting in the death of the person; e. Serious and premeditated maltreatment regulated in Article 355 of the Criminal Code with the following details: Serious and premeditated maltreatment, Serious and premeditated maltreatment resulting in the death of the person. Apart from that, it is also regulated in Chapter XX (Abuse) by Article 358 of the Criminal Code, people who take part in raids/attacks are carried out by several people. This is very similar to Article 170 of the Criminal Code because fights are generally the use of violence in public. The main problem in writing this thesis is what is the basis for the formulation of Article 351 of the Criminal Code as a crime of persecution and whether the Panel of Judges has properly considered case No. 689/Pid.B/2018/PN Jkt.Sel. The research method used is normative juridical research, namely by collecting and studying books related to the issues discussed. The authors' conclusions 1) that the basis for the formulation of Article 351 of the Criminal Code is a criminal act of persecution, namely intentionally causing bad feelings (suffering), pain (pijn), or injury. From the facts revealed at the trial that the defendant had abused the victim on behalf of FERI SETIAWAN with the results of the examination namely bruises and abrasions on the nose caused by being hit by a blunt object based on Visum Et Repertum from Zahirah Hospital with No. 306/RSZVER/04/2018 April 14 2018 at around 20.10 WIB who carried out the examination was dr. JOHANES SANTOSO as examining doctor on 14 April 2018; 2) that the consideration of the Panel of Judges in the criminal case No. 689/Pid.B/2018/PN Jkt.Sel which stated that the defendant's actions were a crime of persecution, because based on the facts revealed at trial, all the elements of the crime of persecution were indeed fulfilled. Therefore, it is appropriate for the judges' decision to impose a sentence on the defendant. The author's suggestions 1) that if all the elements indicted have been met, it would be better for the panel of judges to decide more than half of the demands of the public prosecutor; 2) The panel of judges must be more careful in providing legal considerations so that the decisions handed down achieve a sense of justice for all parties.